Influence of proinflammatory cytokines on membrane rigidity and morphofunctional state of circulating neutrophils in ovarian tumors - T. V. Abakumova; T. P. Gening; S. O. Gening; I. I. Antoneeva; A. B. Peskov (Медицинская иммунология)
Priming and activation mediated by cytokines cause transient reactions of actin polymerization in neutrophils (Nph), expansion and softening of cells, changes in receptor status, phagocytic ability, and generation of extracellular traps (NET), thus ultimately determining pro- or antitumor phenotype of Nph. To assess the effects of pro-inflammatory cytokines on membrane rigidity and morphofunctional state of neutrophils in benign tumors and ovarian cancer, the levels of circulating cytokines (IL-2, IL-18, MCP-1, TIMP-1), expression of adhesion markers (CD11b), degranulation (CD63), as well as FcãRIIIb receptors promoting phagocytosis (CD16). Ability of neutrophils to phagocytosis and the formation of NET was determined. Statistical evaluation of the data obtained was carried out using Statistica 13.0, Jamovi 1.6.5.0 software. An increase in membrane rigidity was found in benign and malignant ovarian tumors. In benign ovarian tumors, phagocytic activity and expression of CD11b were enhanced. In ovarian cancer, the number of CD11b+Nph and CD63+Nph were increased. Meaanwhile, at initial cancer stage, the ability to form NET predominates, and phagocytic activity increases with advancing ovarian cancer. Serum MCP-1 levels are elevated in benign tumors and at all stages of ovarian cancer. IL-2 is elevated at early stage and in advanced ovarian cancer. The level of IL-18 and TIMP-1 in the serum of patients with benign ovarian tumor did not differ significantly from the norm. Using multiple regression approach, the dependence of neutrophil membrane rigidity on the levels of circulating IL-2, TIMP-1, MCP-1, IL-18 was revealed in benign ovarian tumors, and a direct correlation was found between the neutrophil membrane rigidity and CD11b expression. Only IL-2 was associated with neutrophil membrane rigidity in ovarian cancer. At the same time, the rigidity of the neutrophil membrane directly correlated with CD16, CD63, expression like as with phagocytic index and inversely correlates with the number of traps. A combination of IL-2, MCP-1 and membrane rigidity of circulating neutrophils (based on multivariate analysis) could be used for differential diagnosis of ovarian cancer. Thus, in a benign ovarian tumor, circulating proinflammatory cytokines are associated with increased rigidity of neutrophil membrane and increase in their adhesion capacity. In ovarian cancer, only IL-2 is associated with altered rigidity of circulating neutrophils. Increase of the latter index is accompanied by elevated phagocytic activity and decreased ability to form NET.